Human Resources Transformation in the Digitalization Professional Era in North Sumatera - Lailan Tawila Berampu; Windy Dian Sari (Esensi: Jurnal Bisnis dan Manajemen, 2020)
The readiness of the Province of Sumatera utara in the era of digitalization in the face of free market competition inevitably starts from the transformation of human resources (HR). Digital HR transformation is very important in an era where technological disruption is the usual norm where revolutionary changes occur but also the phenomenon of evolution in organizations. In addition to digitalization, the transition to business with technology at the centre also requires changes in technology, education, skills and organizational innovation. This cannot be denied, including the government in increasing human resources is one way that can be done to be able to compete in the international world. This study is intended to obtain data and information about the transformation of HR in Sumatera utara in order to increase competitiveness in the digital era. The transformation of HR in Sumatera utara in the digital era was shaped by the dimensions of the technology and innovation.